The Determinants of Demand for Luxury Goods among Youth in Indonesia - Rakhmanto, Puji Sigit; Saudi, Mohd Haizam Mohd; Razimi, Mohd Shahril Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
In modern times, luxury products are available for all the customers beside rich and elite peoples of the society. Prior to that the luxury was only linked with the things such as watches, cars and villas. A lot of changes occurred in the meaning of luxury. Now a day’s people hold more discretionary income and different peoples of the society satisfy their needs by purchasing products of luxury brands. For this reason, luxury is linked with experimental and emotional value. Purchase of luxury items by the people is because of displaying their status in a society. Different customers in a society purchase product for similar reasons. A main purpose of this study is to analyse the effect of different factors which affect the purchase intention of the consumers such as the quality, self-identity, and price of the luxury brands in the context of Indonesian youth. The main objective of the research is to determine the influence of self-identity value, quality and price in determinants of why youth choose original luxury products. The first two determinants are shown to have a positive correlation whilst the last determinant has a negative impact. This indicates that whilst choices are guided by self-identity value and quality of luxury goods, price remains an important discouragement. Thus, it provides insights into the mindset of Indonesia youth in terms of their affinity for luxury goods.